Modernisasi dan pelestarian perkembangan metode dan teknik penulisan aksara Bali. - Suasta, I. B. Made.; Rupa, I Wayan.; Mayun, Ida Bagus.; Proyek Pengkajian dan Pembinaan Nilai-Nilai Budaya (Indonesia) (Departemen Pendidikan dan Kebudayaan RI, 1991)
Development of modern methods for writing Balinese script; conservation of Balinese script; religious aspects of Balinese script to Balinese people; survey.
"Diterbitkan oleh Proyek Pengkajian dan Pembinaan Nilai-Nilai Budaya, Direktorat Sejarah dan Nilai Tradisional, Direktorat Jenderal Kebudayaan, Departemen Pendidikan dan Kebudayaan"--P. iii.
"Penulis, I.B. Made Suasta, I.B. Mayun, Wayan Rupa"--P. iii.
Includes bibliographical references (p. 65-69).
Development of modern methods for writing Balinese script; conservation of Balinese script; religious aspects of Balinese script to Balinese people; survey.
Keywords: Balinese language / Writing.; Inscriptions, Balinese. / http://id.loc.gov/authorities/subjects/sh85066577; Balinese language / Religious aspects / History.; Writing, Balinese.